Adequacies of skin puncture for evaluating biochemical and hematological blood parameters in athletes - Nunes, L. A.; Gandra, P. G.; Alves, A. A.; Kubota, L.; de Macedo, D. (Clinical Journal of Sport Medicine, 2006)
Objective: The authors tested the effect of blood sampling (skin versus venous puncture) on some biochemical and hematological blood parameters in athletes to answer whether skin puncture could be used as a substitute for venous puncture.